Strategi Kebijakan Publik Melalui Program Pengentasan Kemiskinan di Era Pemerintahan Jokowi - Novi Dianita Sari; Nurvita Diah Rahayu; Binti Saniatu Salimah; Nur Muhammad Hima Firmansah; Novi Khoiriawati (FEB Universitas Maritim Semarang, 2024)
Poverty is a complex and ongoing social problem that requires an integrated and sustainable approach. The problem of poverty impacts various aspects of people's lives, so it is important to overcome the problem of poverty. The aim of this research is to describe public policy strategies in overcoming poverty. The research approach used is a qualitative approach with the data used in the form of secondary data sourced from documents, Central Statistics Agency (BPS), research journals, articles and relevant sources. The data analysis technique is inductive based on the data obtained, then analyzed in relation to public policy strategies in overcoming poverty. The results of this research show that public policy strategies have been successful and effective in reducing poverty levels through the leadership policies of Joko Widodo and Jusuf Kalla including the Prosperous Family Savings Program (SKS), the Smart Indonesia Program (PIP), the Healthy Indonesia Program, then during Joko's leadership period Widodo and Ma'ruf Amin with the Direct Cash Assistance (BLT) program.